2019
DOI: 10.3168/jds.2019-16652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental butyrate and weaning on rumen fermentation in Holstein calves

Abstract: tended to have a greater total VFA concentration (35.60 ± 11.4 vs. 11.90 ± 11.8 mM) but mean rumen pH was unaffected (6.25 ± 0.22 vs. 6.17 ± 0.21, respectively). Between PRE-S (wk 6) and POST-S (wk 9), calf starter intake increased (250 ± 219 vs. 2,239 ± 219 g/d), total VFA concentrations increased (35.6 ± 11.4 vs. 154.4 ± 11.8 mM), but mean rumen pH was unaffected (6.25 ± 0.22 vs. 6.40 ± 0.22, respectively). Compared with POST-S, POST-B calves had greater starter intake in wk 7, 8, and 9, but POST-B tended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…As a feed additive, butyrate and its derivates have positive effects on animal health and production 31 . Studies further showed that butyrate supplementation increased starter intake and average daily gain in calves 32 and promoted milk fat production of lactating dairy cows 33 . Meanwhile, our previous study indicated that the SB supplementation was able to maintain the rumen pH to a certain extent and mitigated HC‐induced SARA 10 .…”
Section: Discussionmentioning
confidence: 96%
“…As a feed additive, butyrate and its derivates have positive effects on animal health and production 31 . Studies further showed that butyrate supplementation increased starter intake and average daily gain in calves 32 and promoted milk fat production of lactating dairy cows 33 . Meanwhile, our previous study indicated that the SB supplementation was able to maintain the rumen pH to a certain extent and mitigated HC‐induced SARA 10 .…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported different modes of action of SB supplementation in young animals. One study suggested that butyrate might enhance growth performance in young calves by improved feed digestibility [36], while another study proposed that butyrate might enhance the absorption capacity of nutrients by increasing the depth of the crypts and the length of small intestine villi, thus increasing the absorptive surface area, in rats and pigs [37]. In newborn calves, SB was shown to stimulate the development of the rumen [24] and small intestines [25] and enhance the maturation of the intestinal tract (including increased villus size and activities of digestive enzymes) [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the rumen, butyrate confers multiple protective bene ts, such as improving tight junctions, epithelial energy mobilization, and VFA absorption capacity [2]. Studies have shown that butyric acid could lower the rumen pH of calves [38], which can promote the GI colonization with bene cial bacteria [13]. However, our study showed that SB did not affect the rumen pH of the calves, probably because most of the SB bypassed the rumen together with the ingested liquid feed, and DMI, either total or starter, was not affected.…”
Section: Sodium Butyrate Does Not Affect Rumen Fermentation In Calvesmentioning
confidence: 99%